Diseño e implementación de un módulo electrónico para mantenimiento preventivo y predictivo de los motores eléctricos de los Laboratorios de Electrónica de la Universidad Politécnica Salesiana - Sede Quito, Campus Sur, mediante análisis de vibración mecánica - Tene Asimbaya, Pedro Luis (2016)
Electric motors for many years have been very essential for all types of independent production enterprises engaged, however is also used in the education sector and in the Salesian Polytechnic University for student learning, is why passing the years a gradual wear is generated in the internal parts containing an electric motor. The procedure required to assess the state of an engine is based on an analysis of mechanical vibration by an ISO standard setting the levels of severity of an engine can be set to the respective preventive and predictive, which are responsible for identifying potential It presents an engine failure. The following titling project develops a system analysis of mechanical vibration to electric motors electronics laboratories Salesian Polytechnic University campus sur - See Quito, in the first phase of the design and the selection criteria referred to electronic devices and mechanical, according to the technical requirements of the electronic module, the second phase of implementation of the system that connects the transmitter vibration, data acquisition card and the computer, in the third phase includes the development of programming in the LabVIEW software contemplating parameters severity of the ISO 2372 standard by the Sound and vibration toolkit of National Instrument as a tool for the analysis of vibration levels for the four types of electric motors.